Penetapan Harga untuk Peningkatan Penjualan Produk Obat Ambroxol pada PT. XYZFARM Bandung - Risa Mei Simamora; Tiris Sudrartono (Journal of Management and Bussines (JOMB), 2024)
This research aims to test pricing to increase sales of Ambroxol medicinal products at PT. XYZFARM Bandung. Sales data for the drug Ambroxol from January to December 2022 were analyzed using a simple regression analysis method. The research results showed a normal distribution in the sales data for the drug Ambroxol. The research model produces a coefficient of determination of 48.9%, indicating that price contributes 48.9% in explaining variations in the quantity of the drug Ambroxol. Hypothesis testing shows that there is a significant influence between the price of the drug Ambroxol and the quantity sold. The conclusion is that price is an important factor influencing the demand for Ambroxol on the market. These findings provide crucial information for PT. XYZFARM Bandung in making decisions regarding marketing strategies and inventory management for the drug Ambroxol. Keywords: Ambroxol Drug, Pricing, Increasing Sales, Marketing Strategy